Windows Phone 7 Game Development - Dawes, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Windows Phone 7 is a powerful mobile computing platform with huge potential for gaming. With "instant on" capabilities, the promise of gaming on the move is a reality with these devices. The platform is an ideal environment for .NET developers looking to create fun, sophisticated games. Windows Phone 7 Game Development gives you everything you need to maximize your creativity and produce fantastic mobile games. With a gaming device always in your pocket, as a phone always is, this is too good an opportunity to miss!
The Beginning -- Windows Phone and .NET -- XNA -- Getting Started with XNA -- Creating a Game Framework -- User Input -- Sounding Out with Game Audio -- Drawing with Vertices and Matrices -- The World of 3D Graphics -- Further 3D Features and Techniques -- Enhancing Your Game -- The Application Life Cycle -- Silverlight -- Getting Started with Silverlight -- Silverlight Controls and Pages -- Gaming with Silverlight -- Enhancing Your Silverlight Games -- Distribution -- Distributing Your Game -- Running on Other Platforms.
Keywords: Computer science; Computer Science; Computer Science, general